Do leverage decisions mediate the relationship between board structure and insolvency risk? A comparative mediating role of capital structure and debt maturity. (12th November 2020) - Hussain, Rana Yassir; Wen, Xuezhou; Hussain, Haroon; Saad, Muhammad; Zafar, Zuhaib
Abstract : Purpose: Corporate boards monitor managerial decisions as concluded by the monitoring hypothesis. In this scenario, the present study stresses that leverage decisions can be used as a tool to control insolvency risk. Design/methodology/approach: This study aims at investigating the intervention of capital structure and debt maturity on the relationship between corporate board composition and insolvency risk by employing Preacher and Hayes's (2008) approach. The study sample comprises 284 firms from 2013 to 2017. Structural equation modeling is used to study the direct and indirect relationships among study variables. Findings: Results show that debt maturity is a significant mediator between CEO duality and insolvency risk and between board size and insolvency risk relationships. However, the capital structure did not mediate any of the proposed links. Research limitations/implications: This study suggests using more long-term debt to tackle insolvency risk in listed non-financial firms of Pakistan. It is also inferred that decisions regarding debt maturity are more crucial than capital structure decisions because insolvency risk is concerned. Originality/value: This study evaluates the comparative mediating role of the debt maturity and the capital structure. Such role is uncommon in the literature addressing the relationship between governance variables and insolvency risk.